2006
DOI: 10.1080/14622200500431536
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a nurse‐managed perinatal smoking cessation program implemented in a rural county

Abstract: The present study (a) examined the effectiveness of a nurse-managed smoking cessation program, that was totally integrated into routine perinatal care, on the cessation rates of pregnant smokers in a rural community, and (b) assessed the subject characteristics associated with smoking cessation success. Data were collected from a convenience sample of 194 pregnant women who stated that they were smokers at the onset of their pregnancies. The study compared the effects of usual care (n = 93) versus the Smoke Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“… 78 121–123 However, unlike the pooled estimates, some TTM-based studies have also reported increases in CA at various postpartum periods. 121–126 As for 5A-based NoMC interventions, two out of five studies reported increases in PPA at postpartum 79 119 and one at follow-up, 120 respectively, in line with the pooled estimate. However, both Loukopoulou et al and Althabe et al did not find a significant association between this type of intervention and PPA in late pregnancy 117 and postpartum, 136 respectively.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“… 78 121–123 However, unlike the pooled estimates, some TTM-based studies have also reported increases in CA at various postpartum periods. 121–126 As for 5A-based NoMC interventions, two out of five studies reported increases in PPA at postpartum 79 119 and one at follow-up, 120 respectively, in line with the pooled estimate. However, both Loukopoulou et al and Althabe et al did not find a significant association between this type of intervention and PPA in late pregnancy 117 and postpartum, 136 respectively.…”
Section: Resultssupporting
confidence: 68%
“…Four studies evaluated the effect of the TTM-based counselling by nurses, midwives and/or other professionals 78 121–123. Three studies assessed cognitive behavioural therapy (CBT) based counselling 124–126.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty individually randomised controlled trials [35],[37],[38],[41],[43],[45],[46],[48]–[51],[56]–[64], six cluster randomised controlled trials [40],[42],[52]–[55], and four non-randomised controlled trials (which used quasi-randomisation methods) [36],[39],[44],[47] were identified. The majority of studies (n = 20) were conducted in the United States [35]–[38],[41],[43],[45]–[47],[50],[51],[54],[56]–[59],[61]–[64], with five studies conducted in the United Kingdom [39],[42],[49],[53],[60], two in the Netherlands [40],[44], and one study each conducted in Poland [55], Canada [48], and New Zealand [52].…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of an intervention based on an expanded version of the 5A's model (Ask, Advise, Assess, Assist, Arrange) delivered by trained health educators to low income women in rural South-Central Appalachia was associated with increased birthweights and 50% fewer NICU admissions compared to a historical control group (Bailey, 2015). In contrast, a study by Britton et al reported no impact on birth outcomes associated with implementation of a nurse-managed cessation program based upon the 5A's that was completely integrated into prenatal care (Avidano Britton, Brinthaupt, Stehle, & James, 2006;Britton, James, Collier, Sprague, & Brinthaupt, 2013). The BMTF program has also been implemented in Tennessee in which a 61% reduction in LBW among 866 BMTF participants with high levels of participation compared to a birth certificate reference population of women of all income levels was observed (Zhang et al, 2017).…”
Section: Previous Community-level Implementation Studies Of Evidence-based Prenatal Smoking Interventions Focusing On Low-income Populatimentioning
confidence: 97%